Physeal bar resection by modified arthroscopically assisted surgery in a closed osteocavity - Xiao, Han; Li, Miao; Tan, Qian; Ye, Weihua; Wu, Jiangyan; Mei, Haibo; Zhu, Guanghui; Yan, An (Frontiers in Pediatrics, 2023)
Background: Physeal bar resection has been used for partial growth arrest treatment for a decade while removing the bony bar minimally invasively and accurately is challenging. This research aims to illustrate a modified arthroscopically assisted surgery, by which all the procedure was under allinside visualization, without the constant exchange between burring under fluoroscopy, followed by irrigation, suction, and arthroscopy of the canal.We retrospectively reviewed the patients who sustained physeal bar resection under direct all-inside visualization of the arthroscope during 2016-2021. Patients who underwent physeal bar resection with the aid of an arthroscope for identifying the physeal cartilage but not resecting and visualizing the physeal bar simultaneously were excluded from this study.In total, nine patients with ten related joints were included in this study. All the patients were followed up for at least two years. The average following time was 28.5 ± 6.7 months. Eight patients with nine related joints had an improvement of angular deformity, averaging 8.3 ± 6.9 degrees, and one had a worsening of the angular deformity. All the patients had a leg length discrepancy improvement, while four patients still had LLD > 1 cm. The surgery time was 3.1±0.7 hours. There were no postoperative fractures, infections, or intraoperative complications such as neurovascular injury.Using clamps to form a closed osteocavity could make physeal bar resection under all-inside arthroscopic visualization feasible, which is minimally invasive, accurate, and safe.